Butyrate Does Not Protect Against Inflammation-induced Loss of Epithelial Barrier Function and Cytokine Production in Primary Cell Monolayers From Patients With Ulcerative Colitis - Vancamelbeke, Maaike (J Crohns Colitis, 2019)
BACKGROUND AND AIMS: In vitro studies using immortalised cancer cell lines showed that butyrate has an overall positive effect on epithelial barrier integrity, but the physiological relevance of cancer cell lines is limited. We developed epithelial monolayers from human tissue samples of patients with ulcerative colitis [UC] to assess the effect of butyrate on epithelial barrier function. METHODS: A protocol to establish monolayers from primary epithelial cells of UC patients [n = 10] and non-UC controls [n = 10] was optimised. The monolayers were treated with 8 mM sodium butyrate ± tumour necrosis factor alpha [TNFα] and type II interferon [IFNγ] for 48 h. Changes in transepithelial electrical resistance were monitored. Barrier gene expression levels were measured. Inflammatory proteins in the supernatant of the cells were quantified with OLINK. RESULTS: We demonstrated that primary monolayer cultures can be grown within 1 week of culture with robust resistance values and polarised tight junction expression. Butyrate treatment of the cultures increased resistance but was detrimental in combination with TNFα and IFNγ. The combined treatment further induced even higher IL8 mRNA and inflammatory protein secretion than for the inflammatory mediators alone. The observed effects were similar in cultures from patients and non-UC controls, suggesting that there were no patient-specific responses responsible for these findings. CONCLUSIONS: We found that butyrate does not protect against inflammation-induced barrier dysfunction and even worsens its effects in primary epithelial monolayers of UC patients and controls. The basic mechanisms of butyrate should therefore be reconsidered in future studies, in particular in patients with active inflammation and pre-existing barrier defects as is known for UC.